2011
DOI: 10.1089/tmj.2011.0012
|View full text |Cite
|
Sign up to set email alerts
|

A Call for Safer Utilization of Radio Frequency Identification in the e-Health Era

Abstract: The main purpose of this study was to investigate the perceptions of the electromagnetic interference (EMI) caused by radio frequency identification (RFID) with medical devices among hospitals as well as to call the attention of medical institutions to the development of RFID applications. A survey sponsored by the Department of Health of Taiwan was conducted and the target subjects were every hospital in Taiwan (486 in total). The survey topics included testing of RFID interference with medical devices and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Researchers at St. Gallen Canton Hospital in Switzerland reported that high-frequency 13.56 MHz RFID tags would not interfere with the functionality of imaging devices [15] significantly. However, there are reports stating that RFID technology is capable of inducing potentially hazardous incidents in medical devices, especially in implantable pacemakers, defibrillators and critical care equipments [58]. In this study, repetitive experiments were performed in three typical scan sequences with a phantom of standard size to investigate the effects of active RFID tags having on MR imaging quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers at St. Gallen Canton Hospital in Switzerland reported that high-frequency 13.56 MHz RFID tags would not interfere with the functionality of imaging devices [15] significantly. However, there are reports stating that RFID technology is capable of inducing potentially hazardous incidents in medical devices, especially in implantable pacemakers, defibrillators and critical care equipments [58]. In this study, repetitive experiments were performed in three typical scan sequences with a phantom of standard size to investigate the effects of active RFID tags having on MR imaging quality.…”
Section: Discussionmentioning
confidence: 99%
“…However, although several studies have shown that RFID tags may cause side effects to some critical care medical equipments, such as infusion/syringe pumps and implantable pacemakers and so on [57], little attention has been paid to the EMI effects caused by RFID applications in hospitals in the last few years. Considering the RFID technology widely using in healthcare without exploring EMI, studies and evaluations on patient safety affected by EMI should be made urgently [8]. Hospitals should not ignore the possibility of EMI even though the number of incidents reports is low [9].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of e-health also needs technology delivery, which promotes evolution of computing science and information systems. In computing science, scholars appeal the era of safer utilization of radio frequency identification (Liu et al, 2011), the use of a lightweight middleware for an e-health WSN-based system using android technology (Boulmalf et al, 2012), wireless technologies (El Khaddar et al, 2012), cloud-based architecture for e-health wireless sensor networks (Lounis et al, 2012), digital rights management and side channel attacks defense mechanisms for security and privacy in e-health (Papalambrou et al, 2012). In information systems, e-health develops a lot either.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous applications are improving patient care by tracking medical devices, drugs, patients and so on [7][8][9][10][11][12]. However, albeit the advantages, there is one important potential risk: electromagnetic interference with medical devices [13][14][15][16][17][18], because RFID systems emit electromagnetic waves.…”
Section: Reviewmentioning
confidence: 99%